Peran Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat Dalam Upaya Pencegahan Kejahatan Kelompok Remaja Di Bandar Lampung - Angkasa, Nitaria (Universitas Sang Bumi Ruwa Jurai, 2024)
Article 2 of Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia outlines the function of the police in maintaining order and security in society. The problem raised in this research is how to implement Article 3 of the National Police Chief's Regulation Number 7 of 2021 in preventing crimes committed by teenagers. As well as factors inhibiting the implementation of Article 3 of the National Police Chief's Regulation Number 7 of 2021 concerning Bhayangkara as a Builder of Community Security and Order by Bhabinkamtibmas in preventing crimes committed by groups of teenagers. The research method used is a systematic approach used to obtain objective and accurate data in drawing conclusions or solving a problem. factors inhibiting the implementation of Article 3 of the National Police Chief's Regulation Number 7 of 2021 concerning Bhayangkara as a Builder of Community Security and Order by Bhabinkamtibmas in preventing crimes committed by groups of teenagers